ON THE FRACTIONAL INTEGRAL OPERATORS FOR REAL POSITIVE DEFINITE SYMMETRIC MATRIX (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In the present paper fractional integral operators associated with -function for real positive symmetric definite matrix have been discussed. These operators have a wide range of applications in the field of Mathematical Physics and Linear differential equations. A number of special cases of our operators have been mentioned.